Values of some topographic parameters of optic nerve head obtained by Heidelberg retina tomograph II in volunteers and different stage primary open-angle glaucoma patients - B. Anguelov; A. Toshev (Oftalʹmologiâ, 2014)
Purpose: То assess the values of the top five topographic parameters of optic nerve head (ONH) obtained by Heidelberg retina tomograph (HRT) II in volunteers and primary open angle glaucoma (POAG) patients with different stage of perimetric changes.Methods: 73 eyes (38 volunteers at the age of 56 years ±13, 11 men and 27 women) and 170 eyes (90 patients at the age of 66 years ±12, 33 men and 57 women) were examined. We performed the comprehensive ophthalmic examination, standard automated perimetry and measurement of the top five topographic parameters of ONH — rim area, rim volume, cup shape measure, height variation contour и mean RNFL thickness. For the purpose of this study we used HRT II.Results: We determine the values of the investigated topographic parameters of the ONH for healthy volunteers (rim area = 1.68±0.22 mm2, rim volume = 0.44±0.07 mm3, cup shape measure = –0.2±0.06, height variation contour = 0.38±0.08 mm and mean RNFL thickness = 0.24±0.03 mm) and for the patients in different perimetric glaucoma stages (early stage: rim area = 1.52±0.47 mm2, rim volume = 0.38±0.17 mm3, cup shape measure = –0.14±0.1, height variation contour = 0.36±0.09 mm and mean RNFL thickness = 0.22±0.11 mm; moderate stage: rim area = 1.21±0.46 mm2, rim volume = 0.27±0.17 mm3, cup shape measure = –0.09±0.1, height variation contour = 0.36±0.17 mm and mean RNFL thickness = 0.16±0.12 mm; severe stage: rim area = 0.97±0.01 mm2, rim volume = 0.18±0.17 mm3, cup shape measure = –0.06±0.1, height variation contour = 0.28±0.11 mm and mean RNFL thickness = 0.17±0.11 mm). Hodapp-Parrish-Anderson (H-P-A) ’s staging system includes three separate levels (early, moderate and severe) of glaucoma according to visual field defects. Each stage is additionally characterized by the values of the top five topographic parameters of the ONH.Conclusion: Early diagnosis, staging and follow-up of POAG are based on both function and structure assessment. The created value intervals for the top five topographic parameters of the ONH for healthy volunteers and patients in different perimetric stages of glaucoma help and support their right classification. Patients with different level changes require different kind of treatment at different price. In this respect the acquired data is an initial step at the development of POAG staging system based on the topographic parameters of ONH obtained by HRT II.